Interventions to improve dispensing of antibiotics at the community level in low and middle income countries: a systematic review - Samuel Afari-Asiedu; Martha Ali Abdulai; Alma Tostmann; Ellen Boamah-Kaali; Kwaku Poku Asante; Heiman F.L. Wertheim; Marlies Hulscher (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: Inappropriate antibiotic dispensing is one of the key drivers of antibiotic resistance. This review documents the effectiveness of interventions aimed at improving antibiotic dispensing practices at the community level by drug dispensers in low- and middle-income countries (LMIC). Methods: We conducted a systematic search in PubMed, EMBASE, Cochrane Central Register of Controlled Trials and Web of Science (11 November 2019). Studies were included if they reported data on the outcome measure: appropriate dispensing of medicine including antibiotics. The effectiveness of studies was assessed based on quantitative results reported in the studies included. Results: A total of 1158 articles were screened. Thirteen studies from Asia (six), Africa (five) and South America (one) and one study from both Africa and Asia were included in this review. Nine (69.2%) studies reported significant effectiveness of interventions on all or more than 50% of antibiotic-related outcomes. Cochrane Effective Practice and Organization of Care interventions frequently applied were educational meetings (9/13), distribution of educational materials (7/13), educational outreach meetings (7/13), reminders (6/13), local consensus processes (6/13), distribution of supplies (6/14) and clinical practice guidelines (4/14), Nine studies reported on stakeholder involvement. Conclusion: This review shows that it is possible to improve antibiotic dispensing practices at the community level in LMIC. Stakeholders’ involvement was key in the design and implementation of interventions.